2019
DOI: 10.15244/pjoes/92120
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactant Production by a Newly Isolated Enterobacter cloacae B14 Capable of Utilizing Spent Engine Oil

Abstract: The release of spent engine oil into the environment is a common problem that seriously impacts ecological balance of ecosystems. Engine oil is comprised of many petroleum hydrocarbons, in particular polycyclic aromatic hydrocarbons (PAHs). These hydrocarbons are of great attention because of their toxicity, carcinogenicity and mutagenic nature [1]. The removal and recovery of spilled or leaked engine oil can be achieved by physical and chemical means, but these approaches are usually costly, labor intensive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
2
5
1
Order By: Relevance
“…Among all isolates, the F3 had a displacement of all oil types, while, the F1 and F2 only affected the paraffin. In this regard, Ekprasert et al had found that Enterobacter cloacae isolated from petroleumcontaminated soil could produce biosurfactants with 42.2% E24 [28], lower than that for the isolate in the present study. In addition, Patel et al had isolated Staphylococcus epidermidis KX781317 from oilcontaminated sites with different aspects [29].…”
Section: Oil Displacement Processcontrasting
confidence: 71%
“…Among all isolates, the F3 had a displacement of all oil types, while, the F1 and F2 only affected the paraffin. In this regard, Ekprasert et al had found that Enterobacter cloacae isolated from petroleumcontaminated soil could produce biosurfactants with 42.2% E24 [28], lower than that for the isolate in the present study. In addition, Patel et al had isolated Staphylococcus epidermidis KX781317 from oilcontaminated sites with different aspects [29].…”
Section: Oil Displacement Processcontrasting
confidence: 71%
“…The member of Pseudomonas genus (P. aeruginosa, P. stutzeri, and P. mendocina) was obtained in the current study have been widely studied for their production rhamnolipids and lipoproteins biosurfactant, where rhamnolipid biosurfactants have excellent surfactant properties (Cheng et al 2017;Shekhar et al 2018;Twigg et al 2019). Acinetobacter venetianus, Enterobacter cloacae, and Staphylococcus epidermidis have been reported for the production of biosurfactant in previous reports (Bach et al 2003;Hamed et al 2012;Ekprasert et al 2019). The microbial biosurfactants are very important compounds that can be used in various areas of application such as the pharmaceutical application, agriculture, food industries, enhanced oil recovery and environmental restoration (Liu et al 2013;Lovaglio et al 2015).…”
Section: Discussionmentioning
confidence: 76%
“…In our previous work (Ekprasert et al 2019), we found that strain B14 can grow on spent engine oil and perform relatively higher emulsification activity of BS compared to most of the BS produced by other 3 274 E. cloacae strains. The strain B14, therefore, has the potential for bioremediation of petroleum contaminants in the environment.…”
Section: Introductionmentioning
confidence: 84%
“…In our previous work ( Ekprasert et al 2019 ), we used spent engine oil as sole carbon and energy source for microbial growth and found the E. cloacae B14 BS activity to be 42.2%. In this recent work, the use of maltose and yeast extract as the carbon and nitrogen sources can increase the BS activity by up to 79% (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation